EVALUASI KERUSAKAN DAN BIAYA PELAKSANAAN PERBAIKAN GEDUNG AUDITORIUM IAIN KOTA AMBON - Yuni Kartika Akhmad; Tonny Sahusilawane; Maslan Abdin (Jurusan Teknik Sipil, 2024)
This study aims to determine the level of damage that occurred in the repair of the Ambon City IAIN Auditorium Building and also to find out how much it costs to repair the Ambon City IAIN Auditorium Building. so that buildings can operate properly and users feel comfortable, which will further assist in improving building management. In carrying out the maintenance and maintenance of buildings, many things must be done so that the building has a high investment value, in general, the research specifically aims to be able to see the extent to which the implementation and management of building maintenance and maintenance. Damage to buildings occurs due to several factors including, human factors such as negligence in the implementation and use of materials, the quality of concrete factors of natural disasters such as earthquakes, floods, and the influence of weather and climate. For this reason, it is necessary to handle building maintenance where building maintenance is an activity to maintain the reliability, strength, and durability of buildings both in terms of infrastructure and facilities so that buildings are always fit to function as they should. The method used is observation and documentation. This technique is used to determine maintenance and care managers for buildings. From the results of the analysis carried out on the evaluation of repairs and implementation costs of the Ambon City IAIN Auditorium building, the level of damage that occurred to the building was 91% while the repair costs were IDR 49,327,557.66